Prevalence of potentially inappropriate medications and risk of adverse clinical outcome in a cohort of hospitalized elderly patients: results from the REPOSI Study. (21st May 2014) - Pasina, L.; Djade, C. D.; Tettamanti, M.; Franchi, C.; Salerno, F.; Corrao, S.; Marengoni, A.; Marcucci, M.; Mannucci, P. M.; Nobili, A.; REPOSI Investigators
Summary What is known and objective Inappropriate prescribing is highly prevalent for older people and has become a global healthcare concern because of its association with negative health outcomes including ADEs, hospitalization and resource utilization. Beers' criteria are widely utilized for evaluating the appropriateness of medications, and an up‐to‐date version has recently been published. To assess the prevalence of patients exposed to PIMs at hospital discharge according to the 2003 and 2012 versions of Beers' criteria and to evaluate the risk of adverse clinical events, re‐hospitalization and all‐cause mortality at 3‐month follow‐up. Methods This cross‐sectional study was held in 66 Italian internal medicine and geriatric wards. The sample included 1380 inpatients aged 65 years or older. Prescriptions of PIM were analysed at hospital discharge. We considered all patients with complete 3‐month follow‐up. Results and discussion The prevalence of patients receiving at least one PIM was 20·1% and 23·5% according to the 2003 and 2012 versions of the Beers' criteria, respectively. The 2012 Beers' criteria identified more patients with at least one PIM than the 2003 version, although a high percentage of those patients (72·2%) were also identified by the criteria updated in 2003. The main difference in the prevalence of patients receiving a PIM according to the two versions of Beers' criteria involved prescriptions of benzodiazepines for insomnia or agitation, chronic use of non‐benzodiazepine hypnotics, prescription of antipsychotics in people with dementia and oral iron at dosage higher than 325 mg/day. Prescription of PIMs was not associated with a higher risk of adverse clinical events, re‐hospitalization and all‐cause mortality at 3‐month follow‐up in both univariate and multivariate analysis, after adjusting for age, sex and CIRS comorbidity index. What is New and Conclusions This study found no significant effect of inappropriate drug use according to Beers' criteria on health outcomes among older adults 3 month after discharge. Even though these criteria have been suggested as helpful in promoting appropriate prescribing, reducing drug‐related adverse events and associated healthcare costs, to date there is no clear evidence that their application can achieve objective and quantifiable improvements in clinical outcomes. A possible explanation is that both versions of the Beers' criteria have several recognized limitations, one of the main ones being the restricted availability of some drugs in Europe or their limited prescription in everyday clinical practice.